Recovery Following ACL Reconstruction in Male vs. Female Adolescents: A Matched, Sex-Based Cohort Analysis of 543 Patients - Sugimoto, Dai; Micheli, Lyle; Kocher, Mininder; Heyworth, Benton; Maguire, Kathleen (Orthopaedic journal of sports medicine, 2020)
Objectives: The subject of sex-based differences in postoperative recovery after anterior cruciate ligament reconstruction (ACLR) between males and females has been incompletely investigated, with no published comparative analyses specifically in adolescents, which represents the sub-population most affected by ACL injury. The purpose of this study was to compare the 6-month postoperative functional recovery following ACLR between adolescent males and females. We hypothesized that significant differences in postoperative strength, dynamic balance, and functional hop test performance would be seen between the sexes. Methods: All adolescent athletes with closed or closing growth plates who underwent ACLR at a single institution between May 2014 and May 2018 and who underwent functional return-to-sport (RTS) testing between 5-8 months post-operatively were considered for inclusion in this IRB-approved study. To control for potential graft-based rehabilitation differences or donor site morbidity as confounders, only primary ACLRs performed with hamstring autograft were included. Exclusion criteria were previous knee surgery (contralateral or ipsilateral knee), concomitant injury/surgery other than meniscus tear/repair, allograft supplementation, and incomplete medical records. Limb Symmetry Indexes (LSI) for strength (quadriceps, hamstrings, hip abductors, hip extensors), dynamic Y-balance (anterior, posterolateral and posteromedial distance), and functional hop test performance (single hop, triple hop, cross-over hop for distance, and 6-meter timed hop) were compared between groups. To account for differences in physical characteristics between the sexes, one-way between group multivariate analysis of covariance (MANCOVA) was used, with p = 0.05. Results: Amongst 543 subjects (211 male, 332 female), there was no significant difference in age, BMI, incidence of concomitant meniscal pathology, use of regional anesthesia blocks, or time to functional testing between cohorts. However, the height and weight differences, which were expected, were incorporated in the MANCOVA model. Females demonstrated a statistically significantly greater deficit in quadriceps strength LSI compared to males (Table 1). Both males and females demonstrated 33% hamstring strength deficits, with no statistically significant sex-based differences in dynamic balance or functional hop testing, though single leg hop deficits were less severe in males, which trended towards significance (-4% vs. -8%, p=0.062). Conclusion: Females demonstrated greater quadriceps strength deficits than males at 6 months post-ACLR with hamstring autograft, which may translate into greater functional hop testing deficits. Severe hamstring strength deficits persist in both males and females at this time point, underscoring the potential importance of mitigating risk of ACL re-tear by delaying return to play until a later time point with more normalized, symmetric, performance-based metrics.